Wear Rate By Utilizing Asphalt Starbit PG 70 Due To Peat Water Soat - Muthia Anggraini; Krisela Br Simbolon; Alfian Saleh (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2023)
Asphalt Starbit PG 70 is a polymer (elastomer) based modified asphalt. The advantages of Asphalt Starbit PG 70 are resistant to water and weather, thus affecting the construction of highway infrastructure. Construction of highways in peat water areas, where the characteristics of peat water are that it contains high levels of organic matter and iron and has a low pH < 4 – 5, causing performance disturbances and causing pavement damage. The study aimed to analyze the wear value of Starbit asphalt due to peat water immersion for 30 minutes, 24 hours, and 48 hours. The research method is wear testing based on the 2018 Revision 2 Bina Marga Specifications. The results of soaking in peat water for 48 hours experienced an increase in weight loss of 7.37% due to having a high level of acidity which contains lignin compounds in organic matter. Meets the specifications of Highways 2018 Revision 2, namely for a weight loss value of ≤ 20%.